Quality of life of postmenopausal women with teriparatide, denosumab and alendronate: One-year prospective study with a propensity score-matched comparison - Pun Yuet Lam; Prudence Wing Hang Cheung; Sin Ting Lau; Jason Pui Yin Cheung (Journal of Orthopaedics, Trauma and Rehabilitation, 2023)
Background/purpose: To evaluate and compare the effects of parathyroid hormone analogues, receptor activators of nuclear factor kappa-B ligand inhibitors and bisphosphonates on the quality of life of postmenopausal women. Methods: A prospective observational study of 23 matched postmenopausal women was conducted with propensity score analysis on quality of life at one-year follow-up. Visual analogue scale for back pain and outcome scores were carried out as the quality of life or treatment adherence measurements. Results: Teriparatide use was associated with significant improvements in visual analogue scale, EuroQol 5-level 5-dimension general health status and Osteoporosis Assessment Questionnaire physical function, whereas denosumab and alendronate groups only demonstrated improved Osteoporosis Assessment Questionnaire scores but worsened back pain. Baseline average visual analogue scale back pain predicted one-year average back pain progression (partial eta squared = 0.617, p  = 0.001). Conclusions: One-year continuous teriparatide treatment is most effective in improving quality of life outcomes in postmenopausal osteoporotic women. Baseline average visual analogue scale back pain remained the only predictive factor for one-year back pain progression.